2023
DOI: 10.1186/s12888-023-04898-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of eating disorder symptoms in adolescents: a cross-sectional school-based study

Abstract: Purpose To estimate the prevalence of eating disorder symptoms and associated factors in adolescents between 14 and 17 years old. Methods The data were obtained from a cross-sectional school-based study with 782 adolescents from public schools in Caxias do Sul, in Rio Grande do Sul, Brazil, in 2016. The Eating Attitudes Test (EAT-26) was used to investigate eating disorder symptoms. The chi-square test and Poisson regression with robust variance we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A high prevalence of ED was also found in university students [ 21 , 22 ]. In the international context, some studies have reported a higher prevalence of ED in female adolescents [ 23 , 24 , 25 ], while other research has reported no differences of ED between sexes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of ED was also found in university students [ 21 , 22 ]. In the international context, some studies have reported a higher prevalence of ED in female adolescents [ 23 , 24 , 25 ], while other research has reported no differences of ED between sexes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%